Charakterystyka cyklonów tropikalnych występujących na obszarze Tajlandii w poszczególnych porach roku i towarzyszących im warunków pogodowych na podstawie danych z lat 2000-2009 - Krystkowiak, Anna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The aim of this paper is to characterise tropical cyclones occurring in Thailand in different seasons of the year – together with accompanying weather conditions – based on data from the years 2000–2009. It has been found that most cyclones occur during the rainy season, especially in September and October. They usually bring heavy rain and cause numerous floods, although in most cases they come to Thailand in the tropical depression stage, where the wind speed does not exceed 56 km/h. It has been found that cyclones in the area of Thailand pass through different regions and provinces, depending on the season. In the hot season, mainly southern and northern provinces are exposed, whereas in the rainy season northern and north-eastern ones; towards the end of September also the central provinces, while in the cool season – southern ones. In the analyzed period, most cyclones occurred in the provinces of Nong Khai and Nan, being part of the north-east region and the north region respectively, while no cyclone showed up in the eastern region. It has been found that the routes of some cyclones differ from those widely accepted for a given month, and many of them – especially at the end of the rainy season and the cool season – proceeded over the territory of Thailand in the direction of the Andaman Sea and the Bay of Bengal.
Keywords: tropical cyclones; season; weather conditions; movement and track; strength of the cyclone; regions and provinces; Thailand